ANALISI PENGARUH PENYERAPAN TENAGA KERJA DAN TINGKAT PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI KALIMANTAN BARAT TAHUN 2009-2013 - B 01109004, YOHANES HABIBI (Jurnal Pembangunan dan Pemerataan, 2015)
Â  The objective of this research was to analyze the influence of employment and education levels which were categorized into several sectors of the labor force --i.e. the primary sector, secondary sector, tertiary sector, as well as the number of labor force whose education was below elementary school, junior high school, senior high school and above senior high school-- on the economic growth in West Kalimantan. The method used was descriptive quantitative method which is a research method which is used to describe and explain the influence of the number of labor force working in the primary sector, secondary sector, tertiary sector, as well as the number of labor force whose education was below elementary, junior high, and senior high school, and above senior high school on the economic growth in West Kalimantan. The model used in this research was the multiple linear regression and the statistical test. The results of the analysis conducted by the researcher showed a constant value of 5.030122. The value of coefficient of determination (R2) was 0.810470 or 81.04% which indicated the ability of contribution of the number of the labor force working in the primary sector, secondary sector, tertiary sector, as well as the number of labor force whose education was below elementary, junior high, and senior high school, and above senior high school on the economic growth in West Kalimantan, while the rest was influenced by other factors outside of this variable. The calculation and analysis of data indicated that the number of labor force working in the primary sectors was significant with a probability value of 0.0400 which was lower than 0:05; the secondary sector was not significant with a probability value of 0.2684 which was greater than 0.05; the tertiary sector was not significant with a probability value of 0.1565 which was greater than 0:05, the number of labor force whose education was below elementary school was not significant with a probability value of 0.2990 which was greater than 0:05; with elementary school education was significant with a probability value of 0.0070 which was lower than 0.05; with junior high school education was not significant with a probability value of 0.5638 which was greater than 0.05; with senior high school education was significant with a probability value of 0.0351 which was lower than 0.05; and the number of labor force whose education was above senior high school was not significant with a probability value of 0.8910 which was greater than 0.05 regarding the influence on the economic growth West Kalimantan at a reliability rate of 95%. Keywords: Manpower, Education Level, Economic Growth